Implementation of vaginal preparation prior to caesarean section - Adam D Jakes; Annie Bell; Lilian Chiwera; Jilly Lloyd (BMJ Open Quality)
Introduction Surgical site infections following caesarean section are associated with significant morbidity. Vaginal preparation is the cleansing of the vaginal epithelium with an antibacterial solution to reduce the bacterial load and therefore reduce ascending genital tract infection. It is recommended by the WHO and a Cochrane review in 2018 concluded that vaginal preparation immediately before caesarean section probably reduces the rates of postoperative endometritis.Objective To implement vaginal preparation prior to caesarean section at Guy’s and St Thomas’ Hospital NHS Foundation Trust and reduce rates of deep surgical site infections.Methods The protocol (included within the appendices) for vaginal preparation prior to caesarean section was developed after reviewing the available evidence. Two vaginal preparation champions, a midwife and a scrub nurse, were selected to help promote and assist in the implementation. The first implementation cycle included elective and category II and III caesarean sections. To ensure acceptability, 20 women were asked to complete a questionnaire following vaginal preparation. Once the intervention was being performed in >85% of eligible women, the inclusion criteria was expanded to include category I caesarean sections.Results Twelve months following implementation, vaginal preparation was still being performed in 89% of eligible women. The deep surgical site infection rate is now the lowest recorded in the last 6 years. Vaginal preparation prior to caesarean section was acceptable to pregnant women and no adverse effects were reported.Conclusions Vaginal preparation prior to caesarean section has been successfully implemented at Guy’s and St Thomas’ Hospital NHS Foundation Trust. This simple, cheap intervention, performed with readily available materials, is still being performed in a high number of caesarean sections 12 months post-implementation. It has resulted in a reduction in deep surgical site infections. Involvement of key stakeholders and the recruitment of vaginal preparation champions were key to success.